2021
DOI: 10.1002/advs.202001433
|View full text |Cite
|
Sign up to set email alerts
|

Effective Phase‐Alignment for 2D Halide Perovskites Incorporating Symmetric Diammonium Ion for Photovoltaics

Abstract: New structural type of 2D AA′ n−1 M n X 3n+1 type halide perovskites stabilized by symmetric diammonium cations has attracted research attention recently due to the short interlayer distance and better charge-transport for high-performance solar cells (PSCs). However, the distribution control of quantum wells (QWs) and its influence on optoelectronic properties are largely underexplored. Here effective phase-alignment is reported through dynamical control of film formation to improve charge transfer between qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…The inorganic–organic hybrid perovskites solar cells (HPSCs), which are expected to generate renewable resources and resolve global energy problems because of their favorable properties including low cost, superior absorption coefficient, 1,2 appropriate bandgaps, and easy fabrication process 3,4 . The power conversion efficiencies achieved by these materials have steadily improved and currently reach 25.7% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic–organic hybrid perovskites solar cells (HPSCs), which are expected to generate renewable resources and resolve global energy problems because of their favorable properties including low cost, superior absorption coefficient, 1,2 appropriate bandgaps, and easy fabrication process 3,4 . The power conversion efficiencies achieved by these materials have steadily improved and currently reach 25.7% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…MACl is also found to be effective. Zhang et al [50] . showed that MACl can slow down the crystallization of DJ perovskite (BDA)(MA) 3 Pb 4 I 13 (Figure 5 b) and induce its film formation with much lower trap‐state densities, which accordingly leads to enhanced PCEs and environmental stability of the resultant PSCs.…”
Section: Dj Lhp Materials and Devicesmentioning
confidence: 99%
“…in 2009, [ 1 ] perovskite solar cells (PSCs) have rapidly developed in the next decade, achieving a world record power conversion efficiency (PCE) of 25.5%. [ 9–13 ] Besides photovoltaics, perovskites have also demonstrated promising potential for the applications of light‐emitting devices, lasers, photodetectors, and high‐energy radiation detection. [ 14–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Since the first report of using MAPbX 3 as the light-harvesting material for photovoltaics by Miyasaka et al in 2009, [1] perovskite solar cells (PSCs) have rapidly developed in the next decade, achieving a world record power conversion efficiency (PCE) of 25.5%. [9][10][11][12][13] Besides photovoltaics, perovskites have also demonstrated promising potential for the applications of light-emitting devices, lasers, photodetectors, and high-energy radiation detection. [14][15][16][17] While the research interest on perovskite-based optoelectronics is initiated by MAPbI 3 , the state-of-the-art devices usually employ binary/ternary cation and double-halide perovskites (e.g., Cs 1−y−z FA y MA z Pb(I 1−x Br x ) 3 ) as the light-absorbing layer.…”
Section: Introductionmentioning
confidence: 99%